Organisational Participation in Web Based E-markets - Mahajan, Rajesh; Kumar, Sunil (Indian Journal of Marketing, 2004)
Web advertising is generally known as promoting marketing whereby companies inform to its prospective buyers that are currently operating in e-markets. Unlike TV, Cinema, & Other Visual advertisement channels, web is graphic media containing information in the form of text, pictures & Hyperlinks. It provides users easy navigational facility i.e. clicking on a link can take the user to the specific destination/location & allows organizations to interact with the application, through dialog boxes and forms (Stone J Han, 1999). For over a year now, there has been an increasing amount of energy focused towards providing the web as a branding medium (Bloxham, 2001). According to an estimate, the web will capture 50 million users in just 5 years whereas TV & Radio will take 13 years respectively (Jupiter Research, 2000). The Internet population in India for the year 2000 was 3.70 million and it is expected to rise to 23 million by the year 2003(NASSCOM Report. 1997-98). Global economy is at a crossroad. Marketing is expanding from regional to global. Technology has moved ahead. We are now shifting in the age of Information Technology where everything may be done just at the click of the mouse sitting before a computer connecting with Internet.